A CONCEPTUAL FRAMEWORK FOR EVALUATING ARABIC LANGUAGE INSTRUCTION IN THE DEVELOPMENT OF LANGUAGE PROFICIENCY SKILLS - Basmala Basmala; Herdah Herdah (Program Studi Pendidikan Guru Sekolah Dasar Fakultas Pendidikan Ilmu Pengetahuan Sosial dan Bahasa Institut Pendidikan Tapanuli Selatan, 2026)
This study aims to formulate a conceptual framework for evaluating Arabic language learning oriented toward the development of language skills. Evaluation in Arabic language learning should not only measure learners’ mastery of grammatical rules, but also assess their ability to use the language communicatively through listening, speaking, reading, and writing. Therefore, a comprehensive framework is needed to align learning objectives, assessment processes, and language competence development. This study employed a qualitative approach using a library research design. Data were collected from scholarly sources, including peer-reviewed journal articles and academic books related to Arabic language learning evaluation. The data were analyzed through content analysis to identify major concepts and recurring patterns in previous studies. The findings reveal that the proposed framework consists of four main components: fundamental concepts of evaluation, characteristics of Arabic language evaluation, assessment practices for the four language skills, and general principles of evaluation in Arabic language learning. This study contributes by integrating these components into a systematic framework. The framework is expected to guide the development of more comprehensive evaluation practices and support the improvement of learners’ communicative competence in Arabic.